Regenerative agriculture—agroecology without politics? - Tittonell, Pablo; El Mujtar, Veronica; Felix, Georges; Kebede, Yodit; Laborda, Luciana; Luján Soto, Raquel; de Vente, Joris (Frontiers in Sustainable Food Systems, 2022)
Agroecology and regenerative agriculture have plenty in common: soil and ecosystem restoration, reliance on biological interactions and ecosystem services, integration of domestic plants and animals, efficient use of the photosynthetic potential of annual and perennial combinations, amongst other principles. One aspect of agroecology that does not always fit comfortably in the realm of regenerative agriculture is political activism, or the place and emphasis that the ‘social’ dimension takes in the definition of the social-ecological system. This is perhaps one of the reasons why agroecology is more closely associated with peasant movements, for whom claims on rights and access to natural resources are urgent. Regenerative agriculture is an approach increasingly – but not exclusively – adopted by commercial, often large-scale farmers or external investors less concerned with e.g. land tenure security or access to water or genetic resources. Is it possible to think about resilience, adaptability or sustainability without considering their overarching political and social dimensions? Here we explore to what extent different types of regenerative agriculture approaches internalise social and political issues, as well as other principles of agroecology, relying on lexical analysis of the scientific literature (n = 647 publications) and on first-hand engagement of the authors in both agroecology and regenerative farming approaches in different parts of the world. Three types of regenerative agriculture (RA) were identified: ‘philosophy RA’, ‘Development RA’ and ‘Corporate RA’, They share in different degrees the ecological and social principles of agroecology, more easily at farm than at community level. By creating tighter links with the science and movement of agroecology, and fundamentally, by engaging in much needed political debates to foster agri-food transitions and transformations, regenerative agriculture will be able to build broader legitimacy among the relevant stakeholders.